The effects of cocoa producer price on cocoa beans exports in Uganda - Quaye, Joseph Clottey (Kampala: Makerere University, 1994)
Thesis (M. Stat) - Makerere university, 1994.
Includes bibliographical references (p. 102-110)
Keywords: Cocoa trade -- Uganda